PENGARUH PENGGUNAAN MODELPEMBELAJARAN NUMBERED HEAD TOGETHER (NHT) TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN PANCASILA MATERI NILAI- NILAI PANCASILA DI KELAS IV UPTD SD NEGERI CAMPOR 1 - Fitriani, Amalia; Hariyani, Yunita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The purpose of this study was to determine the effect of the numbered head together (NHT) learning model on students' learning outcomes in the fourth grade of SDN Campor 1. The research method used was an experimental method in the form of a one-group pre-test post-test design. The research subject was the fourth grade of SDN Campor 1. Data collection techniques were conducted using test questions in the form of essay questions on Pancasila subjects focusing on Pancasila values. Data analysis techniques included validity testing, reliability testing, normality testing, and paired sample t-test. Based on the paired sample t-test, a significant value of 0.000 < 0.05 was obtained, supported by the data analysis results showing an increase in the average learning outcomes from pre-test (45.86) to post-test (63.10). Consequently, it can be concluded that the use of the numbered head together (NHT) learning model has a positive effect on students' learning outcomes.